State of the art and future trends of optimality and adaptability articulated mechanisms for manufacturing control systems - Jimenez, Jose Fernando (2014)
Nowadays, manufacturing control systems have evolved from reactive and informative decision support system to a proactive and intelligent manufacture management mechanism. Industries require both optimal and adaptive manufacturing processes in order to respond competitively to market requirements. In response, advanced manufacturing control systems are configured as artificial intelligence distributed architectures capable to support environment disturbances. However, these techniques, specifically Multi-agent systems and Holonic Manufacturing Systems, are weak supporting optimal performance. Conversely, Operational Research decision support systems achieve optimality under centralized architectures. Still, these are weak supporting adaptable processes under environmental disturbances. Consequently, researchers recently have focused in articulating optimality and adaptation paradigms in order to construct a robust optimal-wise and adaptable mechanism. This paper surveys the literature in manufacturing control systems that use these articulated adaptable optimal mechanism, constructs a proposal typology according structural features and discusses future possibilities for balancing optimality and adaptability characteristics.